Development of a Sports Moral Character Scale for Primary and Secondary School Learners Based on the Key Competencies of Physical Education and Health - Hongliang Guo; Hongqin Chai; Rui Xue; Lei Yao (SAGE Open)
This study aims to develop a validated scale to measure the sports moral character (SMC) development of Chinese primary and secondary school learners. The primary and secondary indicators in the scale were based on the structural framework of physical education virtues in the “Physical Education and Health Curriculum Standards for Compulsory Education (2022 Edition),” and the measurement questions were designed based on relevant research, 14 senior experts in the fields of school physical education, physical education and training, sport psychology, and ethics assessed the content validity of the scale. The scale consists of three subscales: sports ethics, sports spirit, and sports character, with 33 items embedded in nine dimensions revealed acceptable content validity, internal structure validity, and internal consistency. The SMC scale has a certain degree of scientific validity and reliability and can be used as a valid tool to measure the SMC of primary and secondary school learners.